A Study on Partial Anodontia with and without Syndromes - Bhavin Dudhia; Jigna Shah (Wolters Kluwer Medknow Publications, 2004)
Man has 32 teeth in his permanent set. Many persons fail to develop one or more of their third molars, thereby causing the numbers of teeth to lie between 28 and 32. A small percentage of persons also fail to develop even that allotted number. A failure of tooth to develop is called anodontia. it may be complete or partial (hypodontia). In the past various studies have been carried out on this subject on different aspects. This study was carried out amongst 48 patients with partial anodontia reporting Govt. Dental College and Hospital, Ahmedabad. Various questions were asked to each patient to evaluate the etiopathology. All the patients were examined in dental OPD to find out other oral, facial or systemic malformation. The cases of partial anodontia without syndrome showed the most commonly missing teeth were maxillary lateral incisors and mandibular central incisors. The most common facial malformation found were depressed bridge of the nose and frontal bossing. The most common oral malformations found were overretained deciduous teeth, peg laterals, impacted teeth, high arched palate and tongue tie. The most common syndrome associated with partial anodontia noted was Hypohidrotic Ectodermal Dysplasia.